Identified ureter within structures of residual ovarian syndrome - Begum, Badrunnesa; Akhter, Nasreen; Khanam, Afroza; Begum, Fouzia (Bangladesh Medical Journal Khulna, 2013)
The most common symptom of residual ovarian syndrome (ROS) is chronic pelvic pain. Extensive pelvic adhesions are the typical operative findings, while follicular cysts and corpus luteum hematoma were the common pathological findings of the residual ovaries. However, malignant changes are also recorded. In this case report the ROS was associated with cystic changes in size with extensive adhesion with peitoneuum, omentum and right ureter drawn and impacted within the cyst wall. Opinion of ovarian preservation during hysterectomy for benign indications and the sequelae should be discussed with patient. Our case was carefully managed with adhesiolysis and cystectomy. DOI: http://dx.doi.org/10.3329/bmjk.v45i1-2.13629 Bang Med J (Khulna) 2012; 45 : 36-37